(3OjhGf Ydj Hf CHj WGdHs - (3GdgGTej, GdbQTj, CHh GdMSf, Ydj Hf CHj WGdH Hf YHO GdeWdH, J (B40 (3gs ((3aVd Gddg fXGe GdTQjajs)
(3ChdgG (B:s
(3eHJhQ GdChd, hjHOC CKfGA CTYGQ bGajI GdQGA Hbhdg(B: ...(3jCJj GdoeYRj Ke jeVj dTCfg (B*** (3hjHbi GdoeYnqRi aj CMQ ef GdLeQs
(3BNQgG (B:s
(3ahGddg eG CfSGc CMeO eG eTJ (B*** (3Hj GdYjS aj CQV hLGhQJs
(3JMJ cd HjJ JQLeJg HGdaGQSjI, haj BNQgG OYGA HebOGQ hQbJjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B4(3,U(B296s
(3gOjI GdYGQajf(B:(3L(B1(3,U(B667s
(3cTa GdXfhf(B: (3L(B1(3,U(B802s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs